Methionine restriction inhibits chemically-induced malignant transformation in the BALB/c 3T3 cell transformation assay. (September 2016) - Nicken, Petra; Empl, Michael T.; Gerhard, Daniel; Hausmann, Julia; Steinberg, Pablo
Abstract: High consumption of red meat entails a higher risk of developing colorectal cancer. Methionine, which is more frequently a component of animal proteins, and folic acid are members of the one carbon cycle and as such important players in DNA methylation and cancer development. Therefore, dietary modifications involving altered methionine and folic acid content might inhibit colon cancer development. In the present study, the BALB/c 3T3 cell transformation assay was used to investigate whether methionine and folic acid are able to influence the malignant transformation of mouse fibroblasts after treatment with the known tumour initiator 3-methylcholanthrene. Three different methionine concentrations (representing a −40%, a "normal" and a +40% cell culture medium concentration, respectively) and two different folic acid concentrations (6 and 20 μM) were thereby investigated. Methionine restriction led to a decrease of type III foci, while enhancement of both methionine and folic acid did not significantly increase the cell transformation rate. Interestingly, the focus-lowering effect of methionine was only significant in conjunction with an elevated folic acid concentration. In summary, we conclude that the malignant transformation of mouse fibroblasts is influenced by methionine levels and that methionine restriction could be a possible approach to reduce cancer development. Highlights: Methionine restriction led to a significant decrease of type III foci in the BALB/c 3T3 cell transformation assay (CTA). An increase of the cell transformation rate related to methionine and folic acid enhancement was not detected in the CTA. The CTA seems to be suitable to investigate potential carcinogenic effects of dietary components in vitro.